Strengthening universal HIV ‘test-and-treat’ approaches with social science research - (:unkn) unknown (My University, 2016)
Strengthening universal HIV 'test-and-treat' approaches with social science research The recent publication of new WHO guidelines, including a call for antiretroviral therapy for everyone diagnosed with HIV regardless of CD4 þ cell count and preexposure prophylaxis for people at substantial risk of HIV infection [1], marks an important moment for taking stock of what will be needed to take biomedical HIV prevention approaches to scale, and sustain them. As the author of a recent editorial in The Lancet [2] observes, these guidelines are 'welcome but ambitious. [.. .] No studies exist that address how such a strategy can be executed on a global scale' (p. 1420). We, a multidisciplinary group of social scientists working as part of five large-scale 'universal test-and-treat' (UTT) trials being implemented across six African countries, would argue that successful large-scale expansion of treatment and preexposure prophylaxis will require an indepth understanding of the heterogeneous community and health systems' contexts of the rollout.
Keywords: African Research